THE IMPACT OF CHLORINE CONTENT IN DRINKING WATER ON POPULATION CONSUMPTION - Muradullayeva Mohigul Bobomurod qizi; Ruziyeva Sokhiba Yuldashevna (Journals Park Publishing, 2025)
This article examines the amount of water consumed in regions and cities and its impact on the population. Chlorination is used as the primary method for disinfecting water, and its effectiveness in preventing infectious diseases is highlighted. At the same time, scientific analyses demonstrate that both excessive and insufficient use of chlorine can pose health risks.
Keywords: Drinking water, water supply, disinfection, water quality, sanitary standards, hygiene, infectious diseases, epidemiology, ecology, water purification technologies, toxic effects, water pipelines, WHO standards environmental issues.